PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA INTERAKTIF TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI KERAGAMAN SUKU BANGSA DAN BUDAYA KELAS IV - Rere Anisa Putri; Nurdinah Hanifah; Ani Nur Aeni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study investigates the effect of the Problem Based Learning model assisted by interactive media on the critical thinking skills of 4th grade elementary students in learning about cultural diversity. A quasi-experimental design with a nonequivalent control group was used, involving an experimental class applying Problem Based Learning with interactive media and a control class with conventional teaching. Critical thinking was measured using essay tests based on Ennis’ FRISCO indicators. Results showed that the experimental class’s average critical thinking score increased significantly from 64.69 (pretest) to 84.00 (posttest), whereas the control class rose from 64.13 to 71.91. The N-Gain in the experimental class (55.68%) was in the “moderate” category, markedly higher than the control’s N-Gain (22.02%, “low”). An independent t-test confirmed a significant difference in posttest scores (p < 0.001), indicating the experimental group outperformed the control in critical thinking. The effect size of the Problem Based Learning with interactive media treatment was very large (d ≈ 3.0), about twice that of the conventional method, highlighting the model’s practical effectiveness. These findings demonstrate that Problem Based Learning assisted by interactive media has a strong positive impact on students’ critical thinking skills. The interactive media made abstract cultural concepts more concrete and engaging, fostering deeper analysis and problem-solving. The study concludes that integrating Problem Based Learning with interactive learning media is an effective strategy to enhance critical thinking in elementary social studies, significantly outperforming traditional teacher-centered instruction.